2010
DOI: 10.1055/s-0030-1255647
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant Klebsiella pneumoniae outbreak after endoscopic retrograde cholangiopancreatography

Abstract: The endoscopes used for ERCP can act as a reservoir for the emerging ESBL-producing K. PNEUMONIAE. Regular audits to ensure rigorous application of cleaning, high-level disinfection, and drying steps are crucial to avoid contamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
153
0
30

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(186 citation statements)
references
References 14 publications
3
153
0
30
Order By: Relevance
“…And, with the recent emergence of the "superbug" known as carbapenem-resistant Enterobacteriaceae, or "CRE", infection control in this setting has taken on even more urgency and closer examination [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%
“…And, with the recent emergence of the "superbug" known as carbapenem-resistant Enterobacteriaceae, or "CRE", infection control in this setting has taken on even more urgency and closer examination [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%
“…Even if infection does ensue, it may not be immediately apparent after exposure to the endoscope because of silent transmission and colonization. [4][5][6] In 1 recent endoscopy-associated, multidrug-resistant organism (MDRO) outbreak, investigators found that several patients were asymptomatic carriers of an extended-spectrum b-lactamase-producing Klebsiella pneumoniae for more than 10 months after exposure to contaminated endoscopes. Others presented with symptomatic bloodstream infections or biliary tract infections.…”
Section: Reply To Petersenmentioning
confidence: 99%
“…More cases continued to occur, and investigators were able to harvest the epidemic strain and other MDROs (Morganella morganii and Pseudomonas aeruginosa) on several duodenoscopes, following a change in sampling and culturing protocols. 4 This emphasizes the importance of microbial cultures but also highlights the potential disadvantages of relying solely on cultures, because they are difficult to perform and may not be a reliable indicator of the absence of viable organisms. In the outbreak previously mentioned, 4 253 patients were exposed to multiple MDROs over a period of 9 months, with 16 verified cases of transmission, because cultures failed to identify contaminated endoscopes.…”
Section: Reply To Petersenmentioning
confidence: 99%
See 2 more Smart Citations